An Analysis of Revisions to OAIS and the “Designated Community” in Digital Preservation - Moles, Nathan (Information Technology and Libraries, 2026)
In digital preservation, the concept of a “Designated Community” from the Reference Model for an Open Archival Information System (OAIS) is used to articulate the group or groups of prospective users for whom information is preserved. Concerns have been raised about this concept and its potential implications. However, OAIS has recently undergone a major revision. This study examines the extent to which these revisions address or mitigate concerns regarding the Designated Community. Issues from the literature are grouped into three areas: the concept’s implementation, its potential misapplication, and its incompatibility with the mandates of institutions that serve broad and diverse communities. Major changes related to the Designated Community are identified and considered in relation to these issues. The analysis reveals that the revisions productively contribute to concerns in the first two areas but fail to address the third. The conclusion is that the process of revising OAIS has not drawn from insights into this topic in the literature.